"Elis Regina: Dou o tiro, quem mata é Deus!"— performances da cena e da crítica na construção de uma intérprete do Brasil (1964-1978) - Silva, Robson Pereira da (2020)
This research proposes to investigate the variations between Elis Regina's constructed artistic singularity and the dialogues established by her with a collective network of artists (stage directors, choreographers, musicians, etc.) and music critics and, therefore, of diversified interests in the artistic field in relation to their work and artistic identity. This doctoral thesis has as specific object the artist's works produced between 1974-1978, especially the shows Falso Brilhante (1975) and Transversal do Tempo (1978), in the understanding of the way in which the interpreter was inserted in the public debate through the musical scene (as a space for acting) and produced acts of reporting itself in dialogues with collective issues under the scenic aspect. Such spectacles are inserted in the historical moment of the transition between the dictatorial regime and the initiatives that wished the political reopening, in which dissidents began to emerge in the artistic field about the clashes of memory of the democratic resistance in the country. In this process, the artist was raised as a “iconic” of collective expectations that characterized the symbolization of plural projects in her image. Thus, in the centrality of the figure of the artist in her work, Elis Regina began to debate issues in the cultural and socio-political sphere in a marked way, based on what she had on the scene in a deep dialogue between the interpretations attributed to her and the desire to report to yourself (within the limits of producing a narrative and interpretation about your historical experience). The proximity axis between the works chosen here is based on the artist's experience in dialogues and issues with issues of Brazil of her time; in a historical and evaluative reflection that aimed at transition, permanence and the projection of transformations. In these terms, the warp of the text presented here seeks to understand the process of struggles of representations experienced by Elis Regina linked to his reflections on the social role of the artist in dialogue with his interlocutors inserted in the artistic field, in the face of the period of political reopening and the effects of the military dictatorship in the country (1964-1985).